Activity of the Bacillus thuringiensis NprR–NprX cell–cell communication system is co‐ordinated to the physiological stage through a complex transcriptional regulation. Issue 1 (6th March 2013) - Dubois, Thomas; Perchat, Stéphane; Verplaetse, Emilie; Gominet, Myriam; Lemy, Christelle; Aumont‐Nicaise, Magali; Grenha, Rosa; Nessler, Sylvie; Lereclus, Didier
Summary NprR is a quorum sensor of the RNPP family found in bacteria of the Bacillus cereus group. In association with its cognate peptide NprX, NprR controls the expression of genes essential for survival and sporulation of Bacillus thuringiensis during its necrotrophic development in insects. Here, we report that the nprR–nprX genes are not autoregulated and are co‐transcribed from a σA‐dependent promoter (PA) located upstream from nprR. The transcription from PA starts at the onset of the stationary phase and is controlled by two transcriptional regulators: CodY and PlcR. The nutritional repressor CodY represses nprR–nprX transcription during the exponential growth phase and the quorum sensor PlcR activates nprR–nprX transcription at the onset of stationary phase. We show that nprX is also transcribed independently of nprR from two promoters, PH and PE, dependent on the sporulation‐specific sigma factors, σH and σE respectively. Both promoters ensure nprX transcription during late stationary phase while transcription from PA has decreased. These results show that the activity of the NprR–NprX quorum sensing system is tightly co‐ordinated to the physiological stage throughout the developmental process of the Bacillus.